Uma proposta interdisciplinar no ensino de astronomia: automa??o microcontrolada dos controles equatoriais de lunetas e telesc?pios - Pereira, Filipe Nunes Vasconcelos (2023)
The present work brings up the possibility of working with Physics concepts through the construction of an instrumentation automation used in Astronomy. The educational products generated with this work are an electronic device capable of guiding spyglasses and telescopes for the observation of objects inside and outside the Earth's atmosphere, and a manual for the production of didactic spyglasses. Through these products, it is intended to promote study possibilities in Physics, in subjects such as optics and mechanics, and in Astronomy, in subjects such as telescopes and astrometric measurements, with Basic Education students. We present here the procedures adopted in the development of educational products, such as the materials used and the stages of their respective production. We also bring didactic aspects that involve learning through technological resources, in addition to the intervention in the school where the application of an activity in high school classes was proposed, in the two school units of College Augusto Comte (headquarters and branch), in the city of Salvador, Bahia. This activity, which had the first part of its culmination, carried out in the main project of the network in the area of ??Natural Sciences and its technologies: the Science Fair. Finally, we list the results of the productions carried out in the activity and analyze the importance of investing in Astronomy studies and basic concepts of Electronics, as means for a better understanding of Physics.